Le couvent de la Visitation Sainte-Marie de Fourvière (Lyon, Rhône) - Catherine Guégan (In Situ)
Property of the Hospices civils of Lyon, the former convent of the Visitation Sainte-Marie de Fourvière is one of the first works of Pierre-Marie Bossan in Lyon. Its transformation in warehouse for their archives in the middle of 1970s led to important modifications of its structure. From ancient sources and from rare recent studies, this article suggests redrawing the main stages of its construction and its internal development, by insisting more particularly on the decoration of the church. It is indeed there that already assert themselves in their plenitude the main elements of the decorative vocabulary of the architect, the theory of which will be transcribed at the end of the 19th century by his first biographer, Félix Thiollier.